PENGARUH MOTIVASI, KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA KARYAWAN SERTA DAMPAKNYA PADA KINERJA PERUSAHAAN - Erlin Dolphina (Semantik, 2012)
This research aims at analyzing the influence of job motivation, leadership, and corporate culture toward employee job satisfaction, and their impact to the corporate performance. The proposed hypotheses: The job motivation have significance influence to the employee’s job satisfaction, The leadership have significance influence to the employee’s job satisfaction, The organizational culture have significance influence to the employee’s job satisfaction, The work motivation have significance influence to the corporate performance, The leadership have significance influence to the corporate performance, The organizational culture have significance influence to the corporate performance, The employee’s jobsatisfaction have significance influence to the corporate performance. The result of the research has evidenced that jobmotivation, leadership, and organizational culture are significantly related to the employee’s job satisfaction. Leadership,however, is negatively related to the employee’s job satisfaction. Job motivation is not significantly related to the corporateperformance influenced by the intervening variable is employee’s job satisfaction. Leadership and organizational cultureare significantly related to the corporate performance. From this result, there are two main conclutions that can be drawnin this study. First, the job motivation can not be related directly to the corporate performance if it is not connected by theemployee’s job satisfaction variable. And the second conclution is that the leaderhip is negatively related to the employee’sjob satisfaction.Keywords : job motivation, leadership, organizational culture, employee’s job satisfaction, and corporate performance.